Analysis of the Digestion Dynamics and Dietary Risk Assessment of Fluridone in Cotton Fields via QuEChERS Coupled with HPLC - Sen Wang; Ruitong Yang; Yuxuan Li; Zhiqiang Jin; Yutian Xia; Yipin Zhao; Xiaoqiang Han; Guoqiang Zhang; Chunjuan Wang; Ting Ma; Cailan Wu; Desong Yang (Toxics)
Fluridone is a pyrrolidone soil-sealing herbicide that has been widely used in cotton fields in Xinjiang in recent years. The purpose of this study was to establish a method for determining fluridone residues in cotton fields and to perform residue digestion tests, final residue analysis, and dietary risk assessment. Samples were extracted with acetonitrile, purified with primary secondary amine (PSA) and multi-walled carbon nanotubes (MWCNTs), and analyzed by high-performance liquid chromatography (HPLC). The results showed that in a certain concentration range, the concentration and peak area of fluridone showed a good linear relationship (R2 > 0.99), with limit of detection (LOD) and limit of quantification (LOQ) values of 0.00090–0.00108 mg·kg−1 and 0.0030–0.0033 mg·kg−1, respectively. The relative standard deviation (RSD) values of fluridone were 0.46% to 4.57% at the spiked level of 0.1, 0.5, and 1.0 mg·kg−1, respectively. The average daily recovery rate of fluridone was 85.08% to 95.07%. The residual levels of fluridone in cottonseed oil were below the safety threshold, indicating no significant dietary risk to consumers.